ACCURACY OF TIMING IN TSH SAMPLE COLLECTION FOR CONGENITAL HYPOTHYROIDISM SCREENING AT PRIMA MEDIKA GENERAL HOSPITAL DENPASAR - Gusti Ayu Kristalia Mustika Dewi; Didik Prasetya; Diah Prihatiningsih (PT. Jurnal Center Indonesia Publisher, 2025)
Congenital hypothyroidism (CH) is an endocrine disorder that can cause developmental delays if not detected and treated early. Congenital Hypothyroidism Screening (CHS) aims to detect abnormal levels of Thyroid Stimulating Hormone (TSH) in newborns before clinical symptoms appear. The timing of blood sample collection is a critical factor because TSH levels physiologically surge within the first 24 hours of life. This study aims to determine the accuracy of TSH sampling time in CH screening at Prima Medika General Hospital, Denpasar. A descriptive analytical method was used with a total sampling technique involving 105 neonates who underwent CHS from October to December 2024. Secondary data were obtained from laboratory request forms and the Laboratory Information System (LIS). Results showed that 92.4% of samples were collected on the second day of life, which aligns with the ideal window of 48–72 hours, and only 1.9% of neonates had elevated TSH levels. The study concludes that most sample collections met the recommended timing, contributing to valid results and effective CHS implementation. Timely sampling plays a vital role in early CH detection and reflects the overall quality of neonatal laboratory services.